Influence of soil characteristics on rare earth fingerprints in mosses and mushrooms: Example of a pristine temperate rainforest (Slavonia, Croatia). (July 2017) - Fiket, Željka; Medunić, Gordana; Furdek Turk, Martina; Ivanić, Maja; Kniewald, Goran
Abstract: The present study aims to investigate levels and distribution of rare earth elements (REE) in soils, mosses and mushrooms of a pristine temperate rainforest, a non-polluted natural system, in order to characterise their environmental availability and mobility. The multielement analysis of digested soil, moss and mushroom samples was performed by High Resolution Inductively Coupled Plasma Mass Spectrometry. The distribution of rare earths in mosses and mushrooms was found primarily affected by local pedological setting. Mosses displayed a consistent lithological signature with an almost insignificant REE fractionation compared to soils. Mushrooms showed differences in REE concentrations in certain parts of the fruiting body with regard to their main physiological function and indicated a significant impact of soil organic content on the overall REEs uptake. Results of our work highlight the importance of substrate characteristics on the initial levels of REEs in mosses and mushrooms. Moreover, this study provides baseline data on the rare earth element levels in mosses and mushrooms growing in a pristine forest area characterised by naturally elevated REE levels in the soil. Highlights: Rare earths in soils, mosses and mushrooms of a pristine temperate rainforest. The REE in mosses and mushrooms primarily affected by soil characteristics. Mosses display soil signature with an insignificant REE fractionation. Mushrooms indicate an impact of soil organic content on the REEs uptake.